Effects of Metabolic Syndrome on Cognitive Performance of Adults During Exercise - Guicciardi, Marco; Crisafulli, Antonio; Doneddu, Azzurra; Fadda, Daniela; Lecis, Romina (Frontiers in Psychology, 2019)
The metabolic syndrome (MS) has been associated with poor performances in multiple cognitive domains, as processing speed, visuo-spatial abilities and executive functioning. Exercise is a critical factor for MS people’s vulnerability to cognitive dysfunction, because may be beneficial to reduce cognitive impairment, but limited physical activity and impaired cerebral blood flow in response to exercise have been reported by individuals suffering from MS. Using an attentional interference test, the Bivalent Shape Task (BST) and metaboreflex we analyzed cognitive performance and cerebral oxygenation (COX) in 13 MS people (5 women), and 14 normal age-matched CTL (CTL, 6 women). Five different sessions were administered to all participants, each lasting 12 min: post-exercise muscle ischemia (PEMI) to activate the metaboreflex, control exercise recovery (CER), PEMI+BST, CER+BST, and BST alone. During each session, cognitive performance was assessed by response times and response accuracy with which participants make the decision and COX was evaluated by near infrared spectroscopy with sensors applied in the forehead. Compared to CTL, MS group performed significantly worse in all sessions (F = 4.18; p =.05; ES =.13): their poorest performance was observed in the BST alone session. Moreover, when BST was added to PEMI, individuals of the CTL group significantly increased their COX compared to baseline (103.46±3.14%), whereas this capacity was impaired in MS people (102.37%±2.46%). It was concluded that: 1) MS affects cognitive performance; 2) people with MS were able to enhance COX during exercise, but they impair their cerebral oxygenation when an attentional interference task was added.